2011
DOI: 10.1177/0022034510389178
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Role of the S1P/S1PR Axis in Health and Disease

Abstract: Sphingosine-1-phosphate (S1P) is a pleiotropic sphingophospholipid generated from the phosphorylation of sphingosine by sphingosine kinases (SPHKs). S1P has been experimentally demonstrated to modulate an array of cellular processes such as cell proliferation, cell survival, cell invasion, vascular maturation, and angiogenesis by binding with any of the five known G-protein-coupled sphingosine 1 phosphate receptors (S1P1-5) on the cell surface in an autocrine as well as a paracrine manner. Recent studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 156 publications
3
89
0
Order By: Relevance
“…This may appear to contradict our earlier fi ndings; however, radiation pneumonitis and RIF are time-separate events with no active fi brogenesis going on at the pneumonitis stage of RILI. In fact, current fi ndings are well supported by the known profibrotic (36)(37)(38) and proliferative ( 40,42,43 ) role for the SphK1-S1P signaling axis, refl ecting the increased remodeling, the hallmark of fi brogenesis, in RIF lungs.…”
Section: Myriocin Interferes With Tgf-␤ Signaling By Inhibiting Sphk1supporting
confidence: 64%
“…This may appear to contradict our earlier fi ndings; however, radiation pneumonitis and RIF are time-separate events with no active fi brogenesis going on at the pneumonitis stage of RILI. In fact, current fi ndings are well supported by the known profibrotic (36)(37)(38) and proliferative ( 40,42,43 ) role for the SphK1-S1P signaling axis, refl ecting the increased remodeling, the hallmark of fi brogenesis, in RIF lungs.…”
Section: Myriocin Interferes With Tgf-␤ Signaling By Inhibiting Sphk1supporting
confidence: 64%
“…The generation of S1P by SK1 can exert its signaling effects through two routes. In the first, S1P is exported to the outer leaflet via transporter proteins (8,9), where it can act on any of five identified G-protein-coupled receptors (S1P receptors 1-5) (10). Alternatively, S1P is also thought to function as an intracellular signaling molecule acting directly on intracellular targets.…”
mentioning
confidence: 99%
“…Among these, S1P 1 and S1P 2 are widely expressed in most tissues; S1P 3 is highly expressed in the heart, lung, spleen, kidney, intestine, and diaphragm; S1P 4 is specifically expressed in lymphoid tissues and is highly expressed in blood cells, whereas S1P 5 is restricted to the brain and skin and is highly expressed in natural killer cells (Aarthi et al, 2011). Existing studies have shown that the S1P/sphingosine-1-phosphate receptor (S1PR) axis plays critical roles in a wide variety of physiologic and pathophysiological processes, including cancer.…”
Section: Introductionmentioning
confidence: 99%